The Transnational Labor Management Instruments of Multinational Companies: A Polyhedral Reality Still Under Construction - Sanguineti Raymond, Wilfredo (2016)
In the last years, we are witnessing an increasingly intense process of creating instruments on labor management in the transnational scope by the multinational companies, aimed at confronting from its autonomy to the very diverse needs generated by its integrated functioning at the global scale. Currently, the physiognomy of these instruments is not yet sufficiently defined; there are notable differences between one another, depending on the company that promotes them and function that assigns them. The present paper carries out a systematization of the criteria that have been presiding its construction, as well as the lines of evolution that are drawn through them.